Evaluasi fungsi tata hijau pada tempat pemrosesan akhir (TPA) Tlekung, Kota Batu - Soelistyari, Hesti Triana; Alfian, Rizki; Akbar, Mochammad Azkari Hisbulloh (Jurnal Arsitektur Lansekap, 2022)
The problem of waste, especially in the Final Processing Site (TPA) area, is a major issue in Indonesia, so it requires integrated and comprehensive handling. TPA Tlekung, Junrejo District, Batu City has a land area of 6 hectares by applying the sanitary landfill method. The existence of TPA Tlekung is an effort of the Batu City Government in handling municipal waste, but the landscape arrangement for waste management is not optimal. The objectives of this research are to (i) identify the type of vegetation and green system; and (ii) analyze the suitability of the function of reducing pollutants in the TPA Tlekung area, Batu City. Therefore, it is necessary to arrange a landscape in the TPA Tlekung area, in particular by increasing the function of vegetation and green systems as a pollutant reduction agent.